2014
DOI: 10.3329/jbau.v11i1.18209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weeding on the growth, yield and yield contributing characters of mungbean (Vigna radiata L.)

Abstract: An experiment was conducted at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh to assess the effect of weeding on growth, yield and yield contributing characters of mungbean (Vigna radiata L.) cv. BINA mung- 4 during October 2011 to February 2012. The experiment was laid out in a randomized complete block design with four replications. The trial comprised seven treatments namely, T1 = no weeding, T2 = one-stage weeding (Emergence-Flowering), T3 = one-stage weeding (Flowering-Pod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 2 publications
4
11
0
Order By: Relevance
“…Present study also revealed that application of Topstar 80 WP (W 2 ) resulted in highest number of pods plant -1 (18.82), number of seeds pod -1 (12.17) and 1000-seed weight (44.74 g) which was due to weed free condition of the field that supported proper growth and development of the mungbean plants (Table 3). The result is in agreement with the findings of Akter et al (2013). Considering interaction of plant density and weed control, it was evident that plant density of 30 cm×10 cm combined with Topstar 80 WP (D 3 W 2 ) was the best treatment combination for all the yield contributing parameters of mungbean than rest of the others (Table 4).…”
Section: Resultssupporting
confidence: 90%
“…Present study also revealed that application of Topstar 80 WP (W 2 ) resulted in highest number of pods plant -1 (18.82), number of seeds pod -1 (12.17) and 1000-seed weight (44.74 g) which was due to weed free condition of the field that supported proper growth and development of the mungbean plants (Table 3). The result is in agreement with the findings of Akter et al (2013). Considering interaction of plant density and weed control, it was evident that plant density of 30 cm×10 cm combined with Topstar 80 WP (D 3 W 2 ) was the best treatment combination for all the yield contributing parameters of mungbean than rest of the others (Table 4).…”
Section: Resultssupporting
confidence: 90%
“…Moreover, weeds also harbour the viruses and act as a primary source of inoculums, which causes high incidence of virus-like symptoms. Therefore timely control of weeds is essential for high yield in green gram (Akter et al, 2013). Manual weeding (2-3), common practices for weed management in green gram, but it is time consuming, labour intensive and costly option.…”
Section: Introductionmentioning
confidence: 99%
“…The value of GoF which is gotten from this model is 0.3803. GoF as big as 0.38 includes into high category so this model has the good performance and validate the overall model (Akter, Samad, & Zaman, 2013;Husein, 2013;Henderson, Willis, Xiao, & Toffoli, 2016).…”
Section: Predictive Relevance Q − Squarementioning
confidence: 64%
“…The last, the variable of elderly health quality has a value − as big as 0.1009 which means that the diversity of elderly health quality can be explained by the public policy of elderly, nursing function of the elderly, elderly education, and elderly independence as big as 10.09% and the rest 89.91 can be explained by other factors out of the research. The value − as big as 0.26 is classified strong, 0.13 medium, and 0.03 low (Akter, Samad, & Zaman, 2013;Götz, 2010).…”
Section: Coefficient Of Determination R − Squarementioning
confidence: 99%